The Effect of Human Organization Technology on Net benefit HMIS at Pelamonia Hospital Makassar - Mangindara, Mangindara; windarti, sriyani (Miracle Journal of Public Health, 2023)
Law In the Republic of Indonesia Number 44 of 2009 every hospital must record and report on all hospital administration activities in the form of a Hospital Management Information System (HMIS). The successful use of HIMS was assessed using the HOT-Fit method at Hospital TK. II 14.05.01 Pelamonia Makassar has an integrated HIMS but not all units yet because there are still units whose recording and reporting are still manual. This study aims to analyze the effect of Human Organization Technology on HMIS net benefits at Hospital Pelamonia Makassar. This research uses an analytical survey with a cross-sectional study approach and accidental sampling techniques. A total of 448 respondents and a sample of 211 respondents. Data analysis using Microsoft Excel 2007 and WarpPLS 7.0. The results showed that there was no effect of system use (p=0.292), user satisfaction (p=0.150), or structure (p=0.242) on net benefits. Meanwhile, there are influences from the environment (p=0.010), system quality (p=0.001), information quality (p=0.006), and service quality (p<0.001) on the net benefit of HMIS at Pelamonia Makassar Hospital. So it can be concluded that of the seven variables studied, only four variables have an effect, namely environment variables, system quality, information quality, and service quality.